Purification and characterization of a gamma-like DNA polymerase from Chenopodium album L. - Meissner, K (1993)
A DNA polymerase activity from mitochondria of the dicotyledonous angiosperm Chenopodium album L. was purified almost 9000 fold by successive column chromatography steps on DEAE cellulose, heparin agarose and ssDNA cellulose. The enzyme was characterized as a gamma-class polymerase, based on its resistance to inhibitors of the nuclear DNA polymerase alpha and its preference for poly(rA).(dT)12-18 over activated DNA in vitro. The molecular weight was estimated to be 80,000-90,000. A 3' to 5' exonuclease activity was found to be tightly associated with the DNA polymerase activity through all purification steps. This is the first report of an association between a DNA polymerase and an exonuclease activity in plant mitochondria.